Rare Earth Elements (REEs) Potential in Active Geothermal Systems: A Global Review and Regional Study at Mount Slamet, Indonesia - Utama, Peter Pratistha; Pratomo, Septyo Uji; Haty, Intan Paramita; Yoni, Dian Rahma; Afrilita, Afrilita; Pambudi, Setia (BRIN Publishing, 2025)
As global demand for REEs continues to rise due to their strategic role in clean energy technologies, geothermal systems offer an emerging unconventional source. Although data on Indonesian geothermal REEs remain limited, geochemical signals from Mount Slamet provide valuable insights when interpreted alongside global analogs. This study investigates the occurrence, mobility, and potential of rare earth elements (REEs) in the active geothermal system of Mount Slamet, Central Java, Indonesia, with a focus on the hot spring manifestations in Baturraden and Guci using a systematic literature review method based on published research. Baturraden exhibits neutral fluids (pH 6–7) with elevated chloride levels, suggesting enhanced REEs mobilization and strong positive europium (Eu) anomalies under deeper reducing conditions. In contrast, Guci displays more alkaline fluids (pH 8) with lower chloride content, indicating possible meteoric water dilution and lower REEs transport efficiency. These contrasting hydrochemical profiles highlight diverse water-rock interaction mechanisms and fluid pathways. The findings highlight Mount Slamet as a promising candidate for REEs exploration in a volcanic-related geothermal system. This study underscores the urgent need for systematic research on REEs geochemistry in Indonesian geothermal fields to support mineral diversification and sustainable energy transitions.